2011
DOI: 10.1007/s00779-011-0475-0
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation tool for research of user behavior in a realistic mobile environment

Abstract: User behavior is significantly influenced by the surrounding environment. Especially complex and dynamically changing environments (like mobile environment) are represented by a wide variety of extraneous variables, which influence the user behavior in an unpredictable and mostly uncontrolled way. For researchers it is challenging to measure and analyze the user behavior in such environments. We introduce a complex tool -the IVE tool -which provides a unique way of context visualization and synchronization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Similarly, Lumsden et al [45] simulate a city street using a surround sound system in the lab to deliver recorded city street noise, and projections on the floor to create virtual obstacles that the user should try to avoid when walking around the lab. Such simulation of mobility is also found in other lab studies, for example in the work by Wilson et al [62] and Maly et al [48] where test subjects were asked to walk and navigate a track with a number of obstacles, or in Banard et al [6] where they are asked to walk on a treadmill. An example of including the presence and activity of other people in a lab study is found in the work of Leitner et al [44] who simulate a traffic accident to users of an emergency response system.…”
Section: Lab Studiesmentioning
confidence: 85%
“…Similarly, Lumsden et al [45] simulate a city street using a surround sound system in the lab to deliver recorded city street noise, and projections on the floor to create virtual obstacles that the user should try to avoid when walking around the lab. Such simulation of mobility is also found in other lab studies, for example in the work by Wilson et al [62] and Maly et al [48] where test subjects were asked to walk and navigate a track with a number of obstacles, or in Banard et al [6] where they are asked to walk on a treadmill. An example of including the presence and activity of other people in a lab study is found in the work of Leitner et al [44] who simulate a traffic accident to users of an emergency response system.…”
Section: Lab Studiesmentioning
confidence: 85%
“…However, most papers performed usability evaluation in Smart Homes [2,10,11,12,13] and Navigating System [14,15,16,17,18]. Other work performed usability evaluation in other domains [7,9,19,20,21,22] or not really performed any evaluation [8,23,24,25].…”
Section: Literature Reviewmentioning
confidence: 94%
“…Most papers [2,7,9,10,12,13,14,15,16,17,20,21,22] performed usability testing in controlled environments, not in real environments. Moreover, few papers presented specific approaches to usability evaluation for ubiquitous applications and, these approaches that have been identified are not specific to usability tests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response to these issues, researchers use simulations of realistic and natural environments in lab studies. Maly, Mikovec, Vystrcil, Franc, and Slavik (2013), for example, describe a lab experiment to study the influence of stress on the uses of a mobile navigation system for people with visual impairment. In order to simulate a stressful environment, researchers set up auditory and haptic stimuli as well as other barriers on the navigation route in the lab.…”
Section: Challenges In Capturing and Understanding Community In Mobilitymentioning
confidence: 99%